The Formation of Customer Loyalty From Brand Awareness and Perceived Quality through Brand Equity of Xiaomi Smartphone Users in South Tangerang - Rosa Lesmana; Arif Siaha Widodo; Nardi Sunardi (Jurnal Pemasaran Kompetitif, 2020)
The purpose of this research was to determine the effect of Brand Awareness and Perceived Quality on Brand Equity, the effect of Brand Equity on Customer Loyalty, and to find out whether Brand Equity mediates between Brand Awareness and Perceived Quality on Customer Loyalty of the Xiaomi smartphone user in South Tangerang area. The type of the research is quantitative using the factor analysis method, and SEM and the tools used SPSS Amos 23. The unit of analysis in this study is the consumer who uses the Xiaomi smartphone in South Tangerang area. The research design is single cross sectional, a sample size of 150 respondents. The results show that brand awareness does not have a significant effect on brand equity on Xiaomi smartphones in South Tangerang area with a regression coefficient value of -.730 and critical ratio value -1.183. Perceived quality has a significant effect on brand equity on Xiaomi smartphone in the South Tangerang area with a regression coefficient of 0.964 and a critical ratio value of 4,450. Brand equity has a significant effect on customer loyalty of the Xiaomi smartphone in the South Tangerang area with a regression coefficient of 0.590 and a critical ratio value of 5,373. Brand awareness has no significant effect on customer loyalty on the Xiaomi smartphones in the South Tangerang area with a regression coefficient of 0.608 and a critical ratio value of 1.343. Perceived quality has no significant effect on customer loyalty of the Xiaomi smartphones in South Tangerang area with a regression coefficient of -0.164 and a critical ratio value of -0.880. Brand awareness indirectly has no significant effect on customer loyalty through brand equity on the Xiaomi smartphones in South Tangerang area with a regression coefficient of -0.181 and the Sobel test result of -3,000. Perceived quality indirectly has a significant effect on customer loyalty through brand equity on the Xiaomi smartphones in South Tangerang area with a regression coefficient of 0.663 and the results of the Sobel test of 20,165